1988
DOI: 10.1111/j.1365-2559.1988.tb01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Ependymoblastoma: a histological, immunohistological and ultrastructural study of five cases

Abstract: Five ependymoblastomas were studied by means of routine histological techniques, immunohistology and electron microscopy. The tumours were characterized histologically by medium sized, poorly differentiated cells with round or oval nuclei frequently in mitosis and by ependymoblastic rosettes. Reactions for cytokeratin and neurofilament were negative and tubular material positive for glial fibrillary acidic protein was scanty. All five tumors demonstrated positivity for vimentin and S-100 protein. Electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Immunohistochemical profile revealed S-100 and Vimentin positivity in all cases reviewed by Cruz-Sanchez et al 9 12 The authors observed that, in contrast to medulloblastomas, vimentin reactivity in ependymoblastomas was present in most cells throughout the tumour and its intensity was stronger, indicating a later stage of maturation in the latter group. GFAP was found to be absent or only sparsely positive in few tumour cells 12.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Immunohistochemical profile revealed S-100 and Vimentin positivity in all cases reviewed by Cruz-Sanchez et al 9 12 The authors observed that, in contrast to medulloblastomas, vimentin reactivity in ependymoblastomas was present in most cells throughout the tumour and its intensity was stronger, indicating a later stage of maturation in the latter group. GFAP was found to be absent or only sparsely positive in few tumour cells 12.…”
Section: Discussionmentioning
confidence: 92%
“…The histological diagnostic feature of ependymoblastoma is its dense cellularity with numerous distinctive multi-layered rosettes formed by concentric arrangement of cellular rings around small round lumina 3 5 9. The tumour cells are poorly differentiated, oval to spindle shaped with ill-defined cytoplasm and wispy polar processes 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][10][11][12][13][14]16,17,[19][20][21][22][23][24][25][26][27][28][29][30] In our study, we described a 4-year-old girl diagnosed with ependymoblastoma and reviewed the relevant literature. Comparison of these data are possible only to a limited degree, since ependymoblastomas are very rare tumors and have been reported either as single case reports, frequently with no or only scant data on treatment and follow-up, or as part of larger reports on PNETs, and the outcomes usually were not separately elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current concept (McLendon and Gray, 2006), it is a rather rare embryonal tumour characterised by the presence of ependymoblastic rosettes. Ependymoblastomas are characterised by the presence of microvilli, typical cilia and blepharoplasts, and zonulae adherentes (adhesive plaque junctions); thus ependymoblastoma cells resemble those embryonal cells that are already committed to ependymal differentiation (Langford, 1986;Cruz-Sanchez et al, 1988;.…”
Section: Ependymoblastomamentioning
confidence: 99%